however i get a different calculation (27)^-1/3 = 9 (27)^-1/3 = 9 * 2/9 = -2/3 then -2/3 * -27 = 54/3Q = 18/Q
Last edited by mr fantastic; April 9th 2010 at 01:00 AM. Reason: Changed post title
Follow Math Help Forum on Facebook and Google+
Hello, It should work out fine now.
Originally Posted by Bacterius Hello, It should work out fine now. 27^-1/3 is -1/3 then? 2/9*-(1/3) = 2/27 then -2/27 * 27/q = 54/27Q = 2/1q =2/q is that correct
Last edited by matlondon; April 9th 2010 at 08:34 AM.
Originally Posted by matlondon 27^-1/3 is -1/3 then? 2/9*-(1/3) = 2/27 then -2/27 * 27/q = 54/27Q = 2/1q =2/q is that correct No. 27^(-1/3) = 1/3. Try without the minus sign.
Originally Posted by matlondon 27^-1/3 is -1/3 then? 2/9*-(1/3) = 2/27 then -2/27 * 27/q = 54/27Q = 2/1q =2/q is that correct Note that so where the exponents cancel and we are left with 1/3. There is no negative, the negative exponent simply indicates that we have 1 over the value.
View Tag Cloud